Evaluation subgroups of a map and the rationalized $G$-sequence - Maphane, Oteng (Armenian Journal of Mathematics, 2022)
In this paper, we determine, in terms of the Sullivan models, rational evaluation subgroups of the inclusion $ \mathbb{C} P(n)\hookrightarrow \mathbb{C} P(n+k) $ between complex projective spaces and, more generally, the $ G $-sequence of the homotopy monomorphism $ ι: X\hookrightarrow Y $ between simply connected formal homogeneous spaces for which $ π_{*}(Y)\otimes \mathbb{Q}$ is finite dimensional.